Inflammation and Human Ovarian Follicular Dynamics - Boots, Christina E.; Jungheim, Emily S. (Seminars in Reproductive Medicine, 2015)
Inflammation is a biologic process that mediates tissue effects including vasodilation, hyperemia, edema, collagenolysis, and cell proliferation through complex immunologic pathways. In regard to the ovary, inflammation has key physiologic roles in ovarian folliculogenesis and ovulation. On the other hand, inflammatory processes are subject to underlying pathology and, if pushed, proinflammatory conditions may have a negative impact on ovarian follicular dynamics. Obesity and polycystic ovary syndrome (PCOS) serve as examples of conditions associated with chronic endogenous production of low-grade proinflammatory cytokines. Both conditions negatively impact ovarian folliculogenesis and ovulation. The pages that follow summarize the role of inflammation in normal ovarian follicular dynamics and evidence for its role in mediating the negative effects of obesity and PCOS on ovarian follicular dynamics. The review concludes with a summary supporting a role for lifestyle factors that favorably impact inflammatory process involved in obesity and PCOS to improve ovarian function.
Keywords: inflammation; ovarian follicle; lifestyle; obesity; polycystic ovary syndrome